Synthesis characterization and catalytic assessment of zeolite-based catalysts for dimethyl ether production - Catizzone, Enrico; Pantano, Salvatore; Migliori, Massimo (My University, 2017)
Dimethyl ether (DME) has represented a reliable alternative fuel for Diesel engines since decades and, more recently, this compound is receiving a renewed attention also as intermediate for olefins production. Together with many other technologies this application can contribute to reduce the CO2 footprint, mitigating the environmental impact of fossil fuels. Apart from classic liquid phase production process via methanol dehydration, new promising direct gas-phase routes have been proposed, starting from either syngas mixture or via-carbon dioxide hydrogenation. Whatever the route, the acid-catalysed step of methanol dehydration plays a key role in catalyst durability, DME productivity and production costs. Therefore, in view of economically sustainable large-scale gas-phase DME production, low temperature activity, performances and stability are essential factors to consider when developing a reliable catalyst for this step. γ-Al2O3 traditionally plays acid function for direct conversion of methanol to dimethyl ether, but it was also considered as first option co-catalyst for the direct route from syngas coupled with redox catalyst (e.g. Cu/ZnO/Al2O3), promoting the alcohol formation via-CO/CO2 hydrogenation. At reaction temperature traditionally adopted for both direct and indirect routes for (up to 300°C), γ-Al2O3 offers high selectivity towards DME and, due its low acidity, it also inhibits olefins formation. Despite this unchallengeable advantage, this catalyst requires relatively high temperatures and it is rapidly deactivated by strong water adsorption as demonstrated by several studies. As already mentioned some interesting studies were recently carried out on the gas phase process, replacing CO with CO2 during direct route, adding more value to DME as “green chemical” because of the CO2 footprint reduction. In this process, the revers water gas shift reaction significantly increases the amount of produced water, therefore a stable acid function is once more necessary to prevent catalyst deactivation by water adsorption on acid sites. In this concern, exhibiting both higher activity (even at low reaction temperature) and higher resistance to water adsorption, zeolites (manly MFI and modified-MFI) were proposed as catalyst alternative to γ-Al2O3. On the other hand, by using zeolites for selective DME synthesis, both acidity and structure have to be to tuned, in order to mitigate or inhibit undesired reactions such as olefins formation (by hydrocarbon pool mechanism). In fact, zeolites as MFI, BEA, CHA, TON are well-known catalysts for Methanol-to-Hydrocarbons (MTH) processes, catalysed by strong acid sites presents on the framework of these materials. On the other hand, the shape-selectivity offered by zeolites, may permits to act on coke formation, increasing catalyst stability and selectivity. Moreover, investigations are still necessary in order to individuate the suitable channel system to produce DME over zeolites ensuring high DME productivity, selectivity and resistance to carbon deposition. This Ph.D thesis consists of four main objectives. The first objective was to synthesise and characterize zeolites with different channel system (MOR, MTW, EUO, TON, FER, CHA, BEA and MFI), different acidity (aluminium content or Brønsted/Lewis distribution) and different crystals morphology and characterize them by classical analytic techniques as XRD, porosimetry, TG/DTA, SEM, TEM, NH3-TPD and FT-IR. The main results are summarized in Chapter 4. The second objective was to carried out a preliminary screening in order to individuate the most suitable channel system for DME production by methanol dehydration reaction in terms of activity, DME selectivity, stability and coke deposition. 2-dimensional FER structure exhibited reliable catalytic performances whilst 1-dimensional and 3-dimnesional channel system exhibits fast deactivation, low selectivity towards DME or high carbon deposition. Analysis of spent catalysts showed that channel configuration affects strongly both coke composition and location. Commercial γ-Al2O3 was used as benchmark exhibiting high selectivity towards DME but usually lower activity than zeolites. The main results are summarized in Chapter 5. The third objective was to elucidate the role of acid sites (concentration, type, distribution and strength) and crystal size of FER-type catalysts during methanol dehydration reaction. Results showed that acid properties affect strongly catalytic performances. In particular, catalytic activity increases as aluminium content increases but the presence of Lewis acid sites improves catalytic performances in terms of overall turnover frequency of the catalyst. Decreasing crystal size of FER-type material it was possible to reduce drastically the amount of deposited coke. The main results are summarized in Chapter 6. Finally, the fourth objective of this thesis was to evaluate catalytic performances of CuZnZr-zeolite hybrid systems for one-step CO2-to-DME hydrogenation, by assessing the effect of the topology of three different zeolites (MOR, FER and MFI) on the distribution of metal-oxides during catalyst preparation, revealing how such distribution can affect the nature and the interaction of the active sites generated. The catalytic results clearly evidenced a net difference in behaviour among the hybrid systems, both in term of CO2 conversion and product distribution. In particular, CuZnZr-FER catalyst exhibited superior performances as the consequence of better efficiency in mass transferring ensured by the interaction of neighbouring sites of different nature on ferrierite after metal-oxide co-precipitation. A progressive decay of activity was observed during a long-term stability test caused, probably, to strong adsorbing of water on oxygen vacancies where CO2 activated. The main results are sumamrized in Chapter 7.
Dottorato di Ricerca in Scienze e Ingegneria dell'Ambiente, delle Costruzioni e dell'Energiaia, Ciclo XXIX
Keywords: Zeoliti; Catalisi